Characterization of the anti‐factor VIII immunoglobulin profile in patients with hemophilia A by use of a fluorescence‐based immunoassay. (11th December 2014) - Boylan, B.; Rice, A. S.; Dunn, A. L.; Tarantino, M. D.; Brettler, D. B.; Barrett, J. C.; Miller, C. H.; Abshire, T. C.; Kempton, C. L.; Bockenstedt, P. L.; Di Paola, J. A.; Radhi, M.; et al.
Summary Background The development of neutralizing antibodies, referred to as inhibitors, against factor VIII is a major complication associated with FVIII infusion therapy for the treatment of hemophilia A (HA). Previous studies have shown that a subset of HA patients and a low percentage of healthy individuals harbor non‐neutralizing anti‐FVIII antibodies that do not elicit the clinical manifestations associated with inhibitor development. Objective To assess HA patients' anti‐FVIII antibody profiles as potential predictors of clinical outcomes. Methods A fluorescence immunoassay (FLI) was used to detect anti‐FVIII antibodies in 491 samples from 371 HA patients. Results Assessments of antibody profiles showed that the presence of anti‐FVIII IgG1, IgG2 or IgG4 correlated qualitatively and quantitatively with the presence of an FVIII inhibitor as determined with the Nijmegen–Bethesda assay (NBA). Forty‐eight patients with a negative inhibitor history contributed serial samples to the study, including seven patients who had negative NBA titers initially and later converted to being NBA‐positive. The FLI detected anti‐FVIII IgG1 in five of those seven patients prior to their conversion to NBA‐positive. Five of 15 serial‐sample patients who had a negative inhibitor history and had anti‐FVIII IgG1 later developed an inhibitor, as compared with two of 33 patients with a negative inhibitor history without anti‐FVIII IgG1. Conclusions These data provide a rationale for future studies designed both to monitor the dynamics of anti‐FVIII antibody profiles in HA patients as a potential predictor of future inhibitor development and to assess the value of the anti‐FVIII FLI as a supplement to traditional inhibitor testing.